KNOWLEDGE MANAGEMENT OF IT PROFESSIONALS IN BENGALURU CITY - Vivek, Dr. S.; Karuna, Dr. M Meher (The journal of contemporary issues in business and government, 2022)
This article focuses to explore the composition of “Knowledge Management” of IT professionals in Bengaluru city. The article applies data reduction technique using EFA and Simple Linear Regression on a sample of 317 IT professionals and reduces a set of 13 variables converted into three factors. The current research proposes a model of the impact of Management Support for Knowledge Application on Project Knowledge Application and Project Knowledge Application on effective Knowledge Management in the IT industry. The results proved that Management Support for Knowledge Application is significantly impacting on Project Knowledge Application and Project Knowledge Application significantly impacting on effective knowledge management. Hence, the HR managers of IT companies’ can improve the knowledge management of IT professionals.